Penerapan Pemberian Tablet Zat Besi Ditambah Papaya (Carica Papaya Linn) terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Anemia - Amelia Ramadhanty Anindita; Eka Novyriana (Prosiding University Research Colloquium, 2019)
Background: Indonesia is one of ASEAN countries with the highest number of anemia, that is 70%. In Kebumen there were 98.8 % of anemia by mostly being given Fe tablets. Anemia may have negative impact on pregnant mothers and their babies. Consuming Fe tablets and additional food containing vitamin C (like carica papaya) can overcome anemia. Carica Papaya as much as 110 grams contains vitamin C (8,3 mg) that can play an important role in the process of iron substance absorption by changing ferric iron (Fe3+) to be ferro (Fe2+), so that it is easily absorbed in intestine. Objective: To know the increase of hemoglobin level of pregnant mothers with anemia. Method: This study is an analytical descriptive with a case study approach. The participants were 5 pregnant mothers in trimester III with anemia Result: After having application of iron substance tablets and papaya ( carica papaya l) there was . an increase in hemoglobin level of all participants i.e. 1- 2 g / dL. Conclusion: Iron substance tablet plus papaya ( carica papaya l) can increase hemoglobin level.